Influencia de un programa de educación ambiental no forma'I para el manejo adecuado de los residuos sólidos domésticos en la población del barrio de Zaragoza • Moyobamba. - Arevalo Davila, Charlyy (2006)
The present project of investigation was made in the district of Zaragoza of the District and Province of Moyobamba in 2006; and it has as intention to contribute in elevating the knowledge in environmental subjects and the change of attitude for the suitable handling of the domestic solid remainders in the population of the district of Zaragoza; the same one which it counts on a population to the 2006 of 61102 inhabitants (Census 2005 INEI), considering a rate of growth of 3,51 % (INEI). Having as hypothesis" the application of a program of nonformal environmental education in the suitable handling of the domestic solid remainders will influence significantly in the attitude of the settlers ofthe district of Zaragoza", for it primary information through a survey was compiled (pre test), evaluation of environmental indicators, production per capita by house and study of composition of the solid remainders, as much in the group control and experimental group, each one conformed by 49 houses. Soon a Program of nonFonnal Environmental Education for Suitable Manejo of the Domestic Solid Remainders was elaborated and applied, the same one that was evaluated with pos test like a the beginning to both work groups; of which we have the following comparison; in the experimental group the 49, 70% of this population before applying this program knew environmental subjects, and single the 8,74% fulfill the attitude indicators. After applying the program it was observed that the 70,700/o of the experimental group know environmental subjects, and the 11,43% fulfill the attitude indicators. Before the obtained results it is recommended to elaborate and to apply programs of nonformal environmental education of continuous way to educate and to sensitize to the population with respect to the atmosphere and thus to foment the sustainable development.